Os filhos do feminicídio na perspectiva da teoria da proteção integral: a omissão que condena a invisibilidade - Benvegnú, Alice (2024)
The research addresses public policies aimed at orphans of the crime of feminicide in Brazil. The general objective of this scientific investigation is to reveal the projection of feminicide violence, investigate the existence of public policies for children and adolescents who remain from this crime, critically analyzing the responsibility of public authorities in light of the Integral Protection Theory. The first hypothesis is that the children of feminicide are targets of psychological violence given the context in which they are inserted and that the issue is still lagging behind in the country, lacking recognition and attention in the name of the Integral Protection Theory and the context of the Security System. Guarantee of Rights. Orphanhood resulting from feminicide is still an issue that suffers concealment in Brazil and the absence of public protection policies aimed at ensuring the rights of orphans resulting from feminicide condemns children and adolescents who remain from this crime to invisibility, violating the Theory of Comprehensive Protection. The second hypothesis is that public authorities must be held responsible for the lives of feminicide orphans, offering psychological and financial support to victims through public protection policies, especially at the municipal level, under penalty of intensifying retraumatization. The methodology consists of the deductive method and the hermeneutic method. Bibliographic and documentary research techniques were used. Therefore, in order to protect orphans from feminicide from experiencing in a pronounced way the impacts resulting from the context of violence in which they are inserted, public actions and policies must be promoted and executed within the System of Guarantees of Rights, assuming an effectiveness that does not it can be restricted to the normative field, nor to the punitive method as the centrality of solving the problem. Public authorities urgently need to take upon themselves the responsibility of recognizing this reality as a social ill and adopting incisive actions to combat it.